Composite fluoropolymer coatings on the MA8 magnesium alloy surface. (October 2016) - Gnedenkov, S.V.; Sinebryukhov, S.L.; Mashtalyar, D.V.; Nadaraia, K.V.; Gnedenkov, A.S.; Bouznik, V.M.
Highlights: We developed a new method of formation protective coatings. Corrosion resistance increased by 4 orders of magnitude. Wear decreased by 4 orders of magnitude. Composite coatings are resistant to atmospheric corrosion. Abstract: The methods to form protective coatings by the plasma electrolytic oxidation method (PEO) using the superdispersed polytetrafluoroethylene (SPTFE) suspension have been developed. Electrochemical, salt spray corrosion testing, hydrogen evolution, and tribological studies of the composite polymer-containing coatings have been carried out. Models of the coatings structure have been suggested. The obtained results corroborated the increase of the corrosion protection and wear-resistance parameters by more than 4 orders of magnitude for the composite coating in comparison with the base PEO-coating. The fabricated composite coatings are characterised with high antifriction properties due to the presence of polytetrafluoroethylene in the surface layer pores.